Effect of Isobaric Levobupivacaine and Fentanyl versus Isobaric Ropivacaine and Fentanyl as an Adjuvant in Patients Undergoing Transurethral Resection of the Prostate: A Randomised Clinical Study - Sadhana Singh; Varsha Kothari; Anupama Gupta; Puneet Panwar; Sonal Mishra; Pavan Gaurav (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Ropivacaine is a newer local anaesthetic proven to have a lower systemic toxicity profile, particularly in terms of cardiac and Central Nervous System (CNS) toxicity, than the racemic and levorotatory isomers of bupivacaine, especially in elderly patients. Fentanyl, as an adjuvant, enhances analgesia and promotes early postoperative mobility. Aim: To assess and compare the efficacy and safety of isobaric levobupivacaine and fentanyl versus isobaric ropivacaine and fentanyl in patients undergoing Transurethral Resection of the Prostate (TURP) under Spinal Anaesthesia (SA). Materials and Methods: A randomised clinical study was conducted in the Department of Anaesthesia at SMS Medical College and Attached Hospitals, Jaipur, Rajasthan, India, from March 2021 to January 2023. A total of 60 patients ranging in age from 40 to 80 years, scheduled for elective TURP, were enrolled in the present study. The selected patients were randomly assigned into two groups, each consisting of 30 patients. Group A received a dosage of 2.6 cc of 0.75% isobaric ropivacaine (equivalent to 19.5 mg) along with 0.4 cc of fentanyl (equivalent to 20 micrograms). In contrast, group B received a dosage of 2.6 cc of 0.5% isobaric levobupivacaine (equivalent to 13 mg) and 0.4 cc of fentanyl (20 micrograms). The primary outcome measures were the onset of action, duration of sensory-motor block, and postoperative analgesia. Data were analysed using Epi Info version 7.2.1.0 statistical software. The quantitative data collected were summarised using the mean and Standard Deviation (SD). A p-value of less than or equal to 0.05 was considered statistically significant. Results: The majority of patients in the present study were elderly males in both groups. The mean age distribution in group A was 64.27±8.17, and in group B, it was 65.13±7.1. Both groups were comparable and not statistically significant (p=0.634). The mean weight of the two groups was similar, with group A at 64.9±7.49 kg and group B at 63.1±6.96 kg. Both groups were comparable and not statistically significant (p=0.334). The mean height of the patients was 165±4.85 cm in group A and 164±3.83 cm in group B, and it was comparable between the two groups without statistical significance (p=0.145). The duration of sensory block was 241.03±18.88 minutes in group A and 181.5±33.42 minutes in group B. The duration of motor block was 210.7±17.93 minutes in group A and 160±14.82 minutes in group B. Group A demonstrated a significant prolongation of sensory (p<0.001) and motor (p<0.001) block, as well as postoperative analgesia, when compared to 0.5% levobupivacaine with fentanyl. Conclusion: The requirement for rescue analgesia occurred earlier in the levobupivacaine group. Therefore, the use of ropivacaine with fentanyl for spinal anaesthesia in TURP cases is a superior alternative compared to levobupivacaine with fentanyl, as it provides satisfactory quality and duration of block, as well as a longer duration of postoperative analgesia, as assessed by the Visual Analogue Scale (VAS) score and Modified Bromage score.